An Evaluation of Course Materials in the Teaching of English for Academic Purposes - A Case Study at Universiti Pertanian Malaysia - Kam-Lee, Brenda Kim Moy (1984)
Th is study is an attempt to obtain feedback in the form of opinion s from the teachers and students of the BB251 course on the effectiveness of the course materials. Attitudinal information from students' was also obtained as it is felt that this would help towards understanding the teaching/learning situation. A Teachers 'Questionnaire and a Students' Questionaire were administered after the course materials had been used. The study revealed that of the 88 respondents, 92 percent of the students found the course useful. The majority of them felt that the course had helped them read references and textbooks in English while about 50 percent indicated that the course had helped them write in English. The students assessed exercises on vocabulary, structure, comprehension, and writing according to three criteria: interest, usefulness and difficulty. Exercises that demanded manipulative skills were assessed as interesting and not difficult. Exercises that demanded productives kills were assessed as difficult and correspondingly interest level in these exercises fell. Exercises which use non-linear aids were assessed as difficult but interest level tended to be higher than in similar exercises where graphic cues were not used.